Carbon material for catalyst support of polymer electrolyte fuel cell, catalyst layer for polymer electrolyte fuel cell, and fuel cell

A carbon material with specific nitrogen adsorption/desorption isotherm characteristics addresses the overvoltage issue in polymer electrolyte fuel cells, enhancing gas diffusion and reducing overvoltage during large currents for improved fuel cell performance.

JP7605606B2Active Publication Date: 2024-12-24NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020175410
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-19
Publication Date
2024-12-24
Estimated Expiration
2040-10-19

AI Technical Summary

Technical Problem

Existing polymer electrolyte fuel cells experience increased overvoltage during large currents, which hinders their performance and efficiency, particularly in applications like fuel cell vehicles.

Method used

A carbon material for the fuel cell catalyst carrier is developed, characterized by nitrogen adsorption/desorption isotherms exhibiting two hysteresis loops, with specific surface area, hysteresis loop areas, and Raman spectrum parameters that enhance gas diffusion and reduce overvoltage.

Benefits of technology

The carbon material significantly reduces overvoltage during large currents, improving the performance and efficiency of polymer electrolyte fuel cells by enhancing gas diffusion and catalyst utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605606000004
    Figure 0007605606000004
  • Figure 0007605606000005
    Figure 0007605606000005
  • Figure 0007605606000006
    Figure 0007605606000006
Patent Text Reader

Abstract

To provide a new and improved carbon material for a solid polymer electrolyte fuel cell catalyst carrier that can further reduce an overvoltage at a high current, a catalyst layer for a solid polymer electrolyte fuel cell, and a fuel cell.SOLUTION: In a carbon material for a solid polymer electrolyte fuel cell catalyst carrier, in the range in which the relative pressure P / P0 is 0.4 or more, the nitrogen adsorption isotherm shows two hysteresis loops having a first hysteresis loop and a second hysteresis loop.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a carbon material for a catalyst support for a polymer electrolyte fuel cell, a catalyst layer for a polymer electrolyte fuel cell, and a fuel cell. [Background technology]

[0002] A polymer electrolyte fuel cell, which is a type of fuel cell, comprises a pair of catalyst layers arranged on both sides of a solid polymer electrolyte membrane, a gas diffusion layer arranged on the outside of each catalyst layer, and a separator arranged on the outside of each gas diffusion layer. Of the pair of catalyst layers, one catalyst layer serves as the anode of the polymer electrolyte fuel cell, and the other catalyst layer serves as the cathode of the polymer electrolyte fuel cell. In a typical polymer electrolyte fuel cell, a plurality of unit cells having the above components are stacked to obtain a desired output.

[0003] A reducing gas such as hydrogen is introduced into the separator on the anode side. The gas diffusion layer on the anode side diffuses the reducing gas and then introduces it into the anode. The anode includes a catalyst component, a catalyst carrier that supports the catalyst component, and an electrolyte material that has proton conductivity. The catalyst carrier is often made of a carbon material. An oxidation reaction of the reducing gas occurs on the catalyst component, producing protons and electrons. For example, when the reducing gas becomes hydrogen gas, the following oxidation reaction occurs. H 2 →2H + +2e - (E 0 =0V)

[0004] Protons produced by this oxidation reaction are introduced to the cathode through the electrolyte material in the anode and the solid polymer electrolyte membrane. Electrons are introduced to the external circuit through the catalyst support, gas diffusion layer, and separator. After performing work (power generation) in the external circuit, these electrons are introduced to the separator on the cathode side. These electrons are then introduced to the cathode through the separator on the cathode side and the gas diffusion layer on the cathode side.

[0005] The solid polymer electrolyte membrane is made of an electrolyte material having proton conductivity, and introduces the protons generated in the oxidation reaction to the cathode.

[0006] An oxidizing gas, such as oxygen gas or air, is introduced into the separator on the cathode side. The gas diffusion layer on the cathode side diffuses the oxidizing gas, which is then introduced into the cathode. The cathode includes a catalyst component, a catalyst carrier that supports the catalyst component, and an electrolyte material that has proton conductivity. The catalyst carrier is often made of a carbon material. A reduction reaction of the oxidizing gas occurs on the catalyst component, producing water. For example, when the oxidizing gas becomes oxygen gas or air, the following reduction reaction occurs. O 2 +4H + +4e - →2H 2 O (E 0 =1.23V)

[0007] The water produced by the reduction reaction is discharged outside the fuel cell together with the unreacted oxidizing gas. In this way, in a polymer electrolyte fuel cell, electricity is generated by utilizing the energy difference (electric potential difference) between the oxidation reaction and the reduction reaction. In other words, the electrons produced by the oxidation reaction perform work in the external circuit.

[0008] Meanwhile, in recent years, as disclosed in Patent Documents 1 to 5, a technique of using a porous carbon material as a catalyst support has been proposed. As disclosed in Patent Documents 1 to 4, among the porous carbon materials, a porous carbon material having a three-dimensional dendritic carbon nanostructure (hereinafter also referred to as a dendritic carbon nanostructure) has a characteristic structure not found in other carbon materials. Specifically, the dendritic carbon nanostructure has a structure that combines a highly developed pore structure (porous structure) with a large-scale dendritic structure. In other words, by using the dendritic carbon nanostructure as a catalyst support, the catalyst layer has many pores capable of supporting the catalyst component inside the catalyst support. Therefore, the catalyst layer can increase the catalyst support concentration. In addition, the dendritic carbon nanostructure is excellent in gas diffusion in the pores and in gas diffusion in the catalyst layer. As a result, the dendritic carbon nanostructure has a characteristic of being excellent in large current power generation compared to conventional carbon black-based porous carbon materials such as Ketjen black.

[0009] Patent Document 5 proposes a technology in which porous carbon (MgO-templated carbon) material using magnesium oxide nanoparticles as a template is used as a raw material, and the porous carbon is further heat-treated in air and used as a catalyst support. MgO-templated carbon is generally characterized by having uniform pores even in the interior of the material. Furthermore, when MgO-templated carbon is heated in air, the carbon walls that form the pores are oxidized and consumed, reducing the partitions between the pores. In other words, MgO-templated carbon is proposed as a material intended to increase interconnectivity. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] International Publication No. 2014 / 129597 [Patent Document 2] International Publication No. 2015 / 088025 [Patent Document 3] International Publication No. 2015 / 141810 [Patent Document 4] International Publication No. 2016 / 133132 [Patent Document 5] Japanese Patent Publication No. 2015-164889 Summary of the Invention [Problem to be solved by the invention]

[0011] However, when a large current is passed through a polymer electrolyte fuel cell, the overvoltage is likely to become large. For this reason, for example, in fuel cell vehicles that use fuel cells as a power source, the maximum output is important, so there is a strong demand for reducing the overvoltage when a large current is passed. In order to further popularize polymer electrolyte fuel cells, there is a demand to further reduce the overvoltage when a large current is passed.

[0012] Therefore, an object of the present disclosure is to provide a new and improved carbon material for a catalyst support for a polymer electrolyte fuel cell, a catalyst layer for a polymer electrolyte fuel cell, and a fuel cell, which are capable of further reducing overvoltage during large current. [Means for solving the problem]

[0013] The carbon material for a polymer electrolyte fuel cell catalyst support, the catalyst layer for a polymer electrolyte fuel cell, and the fuel cell according to the present disclosure include the following aspects.

[0014] <1> Relative pressure P / P 0 A carbon material for use as a catalyst support for a polymer electrolyte fuel cell, in which a nitrogen adsorption / desorption isotherm exhibits two hysteresis loops, namely, a first hysteresis loop and a second hysteresis loop, when the nitrogen adsorption / desorption isotherm has a molecular weight of 0.4 or more. <2> The two hysteresis loops shown by the nitrogen adsorption / desorption isotherm are the relative pressure P / P 0 The first hysteresis loop exists in the range of 0.87 or more, and the relative pressure P / P 0 has a second hysteresis loop in the range of 0.4 to 0.87 <1> 2. The carbon material for a polymer electrolyte fuel cell catalyst support according to claim 1 . <3> Meet requirements (A), (B), and (C) below; <2> 2. The carbon material for a polymer electrolyte fuel cell catalyst support according to claim 1 . (A) BET analysis of nitrogen adsorption isotherm shows a specific surface area of ​​450 m 2 / g~1500m 2 / g. (B) The first hysteresis loop is a function of the relative pressure P / P 0 Within the range of 0.87±0.03, the difference in adsorption amount △V 0.87 The minimum value of △V 0.87min is less than 20 mL / g. (C) Area △S of the second hysteresis loop 0.4-0.87 is 5mL / g~50mL / g. <4> In addition, the following requirement (D) is met: <3> 2. The carbon material for a polymer electrolyte fuel cell catalyst support according to claim 1 . (D) In ​​the nitrogen adsorption isotherm, the relative pressure P / P 0 The amount of adsorption at 0.99 and the relative pressure P / P 0 The difference in adsorption amount between the adsorption amount at 0.95 and that at △V 0.95-0.99 is 500mL / g to 1100mL / g. <5> In addition, the following requirement (E) is met: <3> or <4> 2. The carbon material for a polymer electrolyte fuel cell catalyst support according to claim 1 . (E) In the Raman spectrum obtained by Raman spectroscopy, -1 ~1700cm -1 The half-width of the G band detected in the range is 45 cm -1 ~70cm -1 It is. <6> <1> ~ <5> 2. A catalyst layer for a polymer electrolyte fuel cell, comprising the carbon material for a polymer electrolyte fuel cell catalyst support according to claim 1. <7> <6> A fuel cell comprising the catalyst layer for a polymer electrolyte fuel cell according to claim 1. <8> The catalyst layer for a polymer electrolyte fuel cell is a catalyst layer on a cathode side. <7> The fuel cell according to claim 1 . Effect of the Invention

[0015] According to the present disclosure, there are provided a new and improved carbon material for a catalyst support for a polymer electrolyte fuel cell, a catalyst layer for a polymer electrolyte fuel cell, and a fuel cell, which are capable of further reducing overvoltage during large current flow. [Brief description of the drawings]

[0016] [Figure 1] 1 is a graph showing a schematic example of a nitrogen adsorption / desorption isotherm for a carbon material for a polymer electrolyte fuel cell catalyst support according to the present disclosure. [Diagram 2] FIG. 2 is an explanatory diagram illustrating an example of a bottleneck type pore. [Diagram 3] 1 is a schematic diagram showing an example of a schematic configuration of a fuel cell according to the present disclosure. [Figure 4] 3 is a photograph showing a measurement method for measuring the branch diameter when observing the carbon material for a catalyst support according to the present disclosure with an SEM. [Diagram 5] FIG. 2 is an explanatory diagram showing a method for measuring the branch diameter of the carbon material for a catalyst support according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] In this disclosure, a numerical range expressed using "~" means a range that includes the numerical values ​​before and after "~" as the lower and upper limits. In addition, when the numerical values ​​before and after "~" are followed by "more than" or "less than," the numerical range does not include these numerical values ​​as the lower or upper limit. In the present disclosure, the term "step" refers not only to an independent step, but also to a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.

[0018] <1. Carbon materials for catalyst supports in polymer electrolyte fuel cells> The carbon material for a polymer electrolyte fuel cell catalyst support according to the present disclosure (hereinafter also referred to as the "carbon material for a catalyst support") has a relative pressure P / P 0In the range of 0.4 or more, the nitrogen adsorption / desorption isotherm shows two hysteresis loops, namely, a first hysteresis loop and a second hysteresis loop. The carbon material for a catalyst support according to the present disclosure can further reduce the overvoltage during a large current.

[0019] It is believed that the dominant factor affecting the overvoltage at high current is the movement resistance (diffusion resistance) of the substances involved in the reaction on the cathode side. Here, the substances involved in the reaction on the cathode side are electrons, protons, oxygen, and water (water vapor) generated by the reaction on the cathode side. Of these substances, electrons and protons are believed to exhibit ohmic behavior. That is, their resistance value is constant and not affected by the magnitude of the current. Therefore, it is believed that the dominant factors of the overvoltage at high current are not electrons and protons, but oxygen and water vapor. In other words, it is believed that the diffusion resistance of the gas flowing inside the cathode (so-called gas diffusion resistance) is the dominant factor of the overvoltage at high current.

[0020] Conventionally, carbon materials have been evaluated based on nitrogen adsorption isotherms. However, the characteristics of carbon materials at high currents could not be fully evaluated by the nitrogen adsorption isotherms alone. For example, Ketjen black is also widely used as a catalyst support for solid polymer fuel cells. Ketjen black has a dendritic structure similar to dendritic carbon nanostructures, and the inside of the branches is also porous. However, the diameter of the branches forming the dendritic structure is thin, and the pore diameter of the pores between the branches is small. For this reason, Ketjen black does not show good gas diffusion properties like dendritic carbon nanostructures. Therefore, the total pore volume can be increased by activating Ketjen black. When activated Ketjen black is used as a catalyst support, the gas diffusion resistance tends to be reduced and the overvoltage at high currents tends to be smaller than Ketjen black before activation. However, it is not sufficient to reduce the overvoltage at high currents. For this reason, the characteristics of carbon materials, especially the characteristics at high currents, could not be fully evaluated by the nitrogen adsorption isotherms that focus only on the adsorption process alone.

[0021] Therefore, the present inventors focused on the nitrogen adsorption isotherm and nitrogen desorption isotherm of the carbon material for the catalyst support in order to evaluate the diffusion resistance of the gas flowing in the cathode. Here, the nitrogen adsorption isotherm and the nitrogen desorption isotherm are obtained by nitrogen gas adsorption measurement. The nitrogen adsorption isotherm is an isotherm on the nitrogen adsorption side, and the nitrogen desorption isotherm is an isotherm on the nitrogen desorption side. Hereinafter, an isotherm combining the nitrogen adsorption isotherm and the nitrogen desorption isotherm (i.e., an isotherm connecting these isotherms) is also referred to as the nitrogen adsorption / desorption isotherm.

[0022] For example, in the case of a conventionally used carrier made of carbon black raw material that has been made porous by activation treatment, pores are formed in the catalyst layer due to the gaps between the carbon black raw material. The pores formed in this catalyst layer reflect the primary particle size of the carbon black. The pore size is usually 30 nm to 40 nm (diameter). For example, Ketjen black after activation treatment has a tendency to increase the area of ​​the above-mentioned hysteresis loop. In other words, the volume ratio of the bottleneck type pores described below increases. When the nitrogen adsorption / desorption isotherm was measured in a catalyst layer using such a carbon black raw material that has been made porous by activation treatment as a carrier, the nitrogen adsorption / desorption isotherm showed one hysteresis loop.

[0023] In addition, the porous carbon material disclosed in Patent Document 5 has a particulate shape. Even if the gas flowability within the particles is improved, the catalyst layer formed of particulate matter has a small pore volume and the pore size is difficult to control. As a result, the gas diffusion within the catalyst layer, not within the particles, is a constraint, and the required level of large current characteristics is not achieved. Therefore, when the nitrogen adsorption and desorption isotherm in the catalyst layer using MgO template carbon as a carrier was measured, the nitrogen adsorption and desorption isotherm showed one hysteresis loop.

[0024] Regarding the carbon material for catalyst carriers that shows the above-mentioned hysteresis loop, the present inventors have considered the relationship between the ideal shape of the catalyst carrier and the hysteresis. In order to reduce the overvoltage at high current, it is sufficient to reduce the mass transfer resistance at high current. For example, in the case of dendritic carbon nanostructures, the branch diameter is about 50 nm to 100 nm, and the branch length is about 50 nm to 200 nm. Therefore, the pores of the catalyst layer are on the order of about 100 nm (width), and the gas diffusion in the catalyst layer is overwhelmingly higher than that of a carrier made of carbon black. From this perspective, it is understood that the fact that the gas diffusion resistance is smaller when the dendritic carbon nanostructure is used as a catalyst carrier on the cathode side than that of a catalyst carrier made of carbon black is due to the three-dimensional form of the dendritic carbon nanostructure.

[0025] In dendritic carbon nanostructures, there are two types of mass transfer: mass transfer in pores present inside the branches themselves (hereinafter also referred to as "intra-branch pores"), and mass transfer in pores formed in the gaps between the branches (hereinafter also referred to as "inter-branch pores"). For example, if gas diffusion to the support surface is insufficient, no matter how high the diffusion of materials in the intra-branch pores is, the large current characteristics cannot be improved. In other words, it is considered that in the catalyst layer, it is prioritized to reduce the resistance to gas diffusion and increase the gas supply to the support surface. It is considered that the pores formed in the catalyst layer are mainly the pores between the branches of the support. Therefore, it is important to make the pore diameter of the inter-branch pores large, to make the pore volume large, and further, to have a sharp distribution width of these.

[0026] It is believed that when the pore diameter and pore volume of the inter-branch pores in a dendritic carbon nanostructure are large, the nitrogen adsorption / desorption isotherm will show a hysteresis loop even in the region of high relative pressure. If a dendritic carbon nanostructure can show such a hysteresis loop, it will be possible to reduce the mass transfer resistance during large currents, and it is predicted that the overvoltage during large currents will decrease. Furthermore, the nitrogen adsorption / desorption isotherm of a dendritic carbon nanostructure shows a hysteresis loop caused by the intra-branch pores. In other words, the dendritic carbon nanostructure of the present disclosure has a high relative pressure P / P 0In the range of 0.4 or more, the nitrogen adsorption / desorption isotherm shows two hysteresis loops, which makes it possible to reduce the mass transfer resistance at high currents, and is considered to reduce the overvoltage at high currents. Note that conventional catalyst layers, such as those using carbon black as a carrier or MgO-templated carbon as a carrier, do not show such hysteresis loops, and therefore are considered to have not sufficiently reduced the overvoltage at high currents.

[0027] In the above, we have taken the dendritic carbon nanostructure as an example, but the relative pressure P / P 0 It is believed that any carbon material for a catalyst support that exhibits two hysteresis loops in the range of 0.4 or more can reduce overvoltage during large current flow, regardless of whether it is a dendritic carbon nanostructure or not.

[0028] As described above, the carbon material for a catalyst carrier according to the present disclosure has a relative pressure P / P 0 In the range of 0.4 or more, the nitrogen adsorption / desorption isotherm shows two hysteresis loops. The carbon material for the catalyst support is not particularly limited. From the viewpoint of easily reducing overvoltage during large current, the carbon material for the catalyst support is preferably a dendritic carbon nanostructure. The dendritic carbon nanostructure, which is a preferred embodiment, will be described below.

[0029] In the present disclosure, the dendritic carbon nanostructure has a structure that combines a highly developed pore structure with a large-scale dendritic structure. That is, the dendritic carbon nanostructure has a dendritic structure formed by branches made of porous carbon. Furthermore, the branches that make up the dendritic structure are branched in a variety of ways. Each branch is long and thick (for example, the branch diameter is about 50 nm to 100 nm (width) and the branch length is about 50 nm to 200 nm). Furthermore, the branch diameter has a relatively small variation. In other words, the branch diameter distribution width is sharp. The dendritic carbon nanostructure has a structure in which thick, long, cylindrical branches are branched in a variety of ways. The inter-branch pores are thick, long, cylindrical pores that correspond to the branch diameter and branch length and are branched in a variety of ways.

[0030] The intrabranch pores also have the same characteristics as the interbranch pores. That is, the intrabranch pores have a thick, long, cylindrical shape and are multiply branched within the branch. For this reason, it is believed that the dendritic carbon nanostructure according to the present disclosure is likely to have a low gas diffusion resistance in the catalyst layer.

[0031] In the present disclosure, the dendritic carbon nanostructure refers to a dendritic carbon structure having a branch diameter of 10 nm to 200 nm or less. The branch diameter is measured by observing SEM images of five fields of view at a magnification of 100,000 times (2.5 μm × 2 μm) using a scanning electron microscope (SEM; Hitachi High-Technologies Corporation SU-9000), measuring branch diameters at 20 points on each image of the field of view, and taking the average value of the measured values ​​of a total of 100 points as the branch diameter value. The branch diameter to be measured is determined by measuring the thickness of the center between two adjacent branch points (the middle part of the branched branch) of the branch of interest (see FIG. 4. In FIG. 4, D indicates the branch diameter per point). Here, a method for measuring the branch diameter will be described with reference to FIG. 5. In FIG. 5, one branch of interest is shown. For this branch of interest, branch points BP1 and BP2 are specified. Next, the thickness (width) of the branch is measured at a position that is a perpendicular bisector BC connecting the identified branch points BP1 and BP2. This measured branch thickness is the branch diameter D per location. The branch length is represented as the distance from the branch point BP1 to the branch point BP2 (see FIG. 5). For example, in the present disclosure, the branch diameter of the dendritic carbon nanostructure is not particularly limited as long as it is within the above range, and may be, for example, about 50 nm to 100 nm. The branch length is also not particularly limited, and may be, for example, about 50 nm to 200 nm.

[0032] Hereinafter, an example of a preferred embodiment of the present disclosure will be described in detail with reference to the drawings. In this disclosure, components having substantially the same functional configurations are denoted by the same reference numerals, and redundant description will be omitted.

[0033] Fig. 1 is a graph showing a schematic diagram of a nitrogen adsorption / desorption isotherm in the carbon material for a catalyst support according to the present disclosure. Fig. 1 shows a preferred embodiment in which the carbon material for a catalyst support is a dendritic carbon nanostructure. The nitrogen adsorption / desorption isotherm shown in Fig. 1 is a function of the relative pressure P / P 0 In the nitrogen adsorption / desorption isotherm shown in FIG. 1, the first hysteresis loop A1 is located on the high relative pressure side, and the second hysteresis loop A2 is located on the low relative pressure side. In the nitrogen adsorption / desorption isotherm shown in FIG. 1, the first hysteresis loop A1 is located on the high relative pressure side, and the second hysteresis loop A2 is located on the low relative pressure side. 0 is in the range of 0.87 or more, and the second hysteresis loop A2 is 0 is in the range of 0.4 to 0.87.

[0034] In general, the nitrogen adsorption isotherm at liquid nitrogen temperature (e.g., 77 K) corresponds to adsorption into pores with smaller pore diameters as the relative pressure decreases. Therefore, the first hysteresis loop A1 is formed by the characteristics of the inter-branch pores, and the second hysteresis loop A2 is formed by the characteristics of the intra-branch pores.

[0035] Here, the mechanism by which the hysteresis loop occurs and a guideline for a carbon material for a carrier using the hysteresis loop as an index based on the mechanism will be described in detail. As shown in FIG. 1, in the desorption curve (nitrogen desorption isotherm), the relative pressure at which the same adsorption volume as the adsorption curve (nitrogen adsorption isotherm) is reached is lower than that of the adsorption. That is, it indicates that the adsorbed nitrogen is difficult to desorb. In the desorption process, the nitrogen will desorb from the route that is easiest to desorb from among the multiple desorption routes (i.e., the route with the largest pores). However, in the desorption process, it indicates that the adsorbed nitrogen will not desorb until the relative pressure drops to a pressure corresponding to the pore diameter. This is the hysteresis phenomenon. The formation of a hysteresis loop corresponds to the adsorption and desorption coinciding at a certain relative pressure, and the effect of the pores disappears. In the present disclosure, for example, the first hysteresis loop A1 disappears at a relative pressure of about 0.87. The first hysteresis loop A1 represents the hysteresis phenomenon caused by the inter-branch pores. Therefore, the fact that the hysteresis caused by the inter-branch pores disappears at a relative pressure of about 0.87 indicates that the pores caused by the branches disappear at about 0.87. In other words, the pore size of a dendritic carbon nanostructure will have a significant distribution width due to the branch diameter and branch length distribution width. As a result, the hysteresis does not close, resulting in a carbon material that does not form two hysteresis loops. Therefore, when the carbon material for a support according to the present disclosure is a dendritic carbon nanostructure, the branch structure of the dendritic carbon nanostructure is required to have a structure with uniform branch diameter and branch length that forms two loops.

[0036] Specifically, a theory has been proposed that a hysteresis loop occurs when a bottleneck pore exists. Figure 2 shows a bottleneck pore 30 as an example of a bottleneck pore formed in a carbon material. The bottleneck pore 30 is composed of a bottle portion 30A and a neck portion 30B that communicates with the bottle portion 30A. The diameter of the bottle portion 30A is larger than the diameter of the neck portion 30B. The neck portion 30B communicates with other pores on the outer surface of the carbon material or within the carbon material.

[0037] In this theory, as will be explained below, a hysteresis loop occurs due to the difference between the adsorption process and the desorption process. That is, in the adsorption process, the adsorption thickness of the nitrogen gradually increases depending on the relative pressure of the nitrogen gas. In this process, the neck of the bottleneck pore is first blocked by adsorption. At that time, even if nitrogen is adsorbed to the bottle portion to a thickness equivalent to the neck portion, the diameter of the bottle portion is larger than the diameter of the neck portion, so the bottle portion is not yet completely filled. In this state, even if the neck portion is blocked, the external pressure and the pressure inside the bottle portion are in equilibrium through the nitrogen adsorption layer. Therefore, if the relative pressure of the nitrogen gas further increases (i.e., the external pressure increases), the pressure inside the bottle portion also increases. Therefore, adsorption equivalent to the external pressure also progresses in the bottle portion, and the nitrogen adsorption layer in the bottle portion becomes thicker even if the neck portion remains blocked. If the external pressure increases further, the bottle portion is finally completely blocked by the nitrogen adsorption layer. That is, even in the bottleneck pore, adsorption progresses in the adsorption process in the same way as in a normal pore structure without a neck portion. However, strictly speaking, when the neck portion is blocked by the nitrogen adsorption layer, at least a part of the nitrogen adsorption layer adsorbed in the neck portion becomes liquid. It is known that the surface tension of such a liquid phase makes the pressure inside the liquid phase (i.e., the pressure inside the bottle portion) slightly smaller than the external pressure. This phenomenon is called the capillary phenomenon. For this reason, in the adsorption isotherm of the bottleneck pore, the relative pressure required to obtain the same amount of adsorption as that of the non-bottleneck pore shifts to a slightly higher value.

[0038] Next, consider the desorption process of nitrogen from a state in which all the pores of the bottleneck pores are filled. In the desorption process, the neck does not open until the external pressure is reduced to a pressure at which the blockage of the neck is released. In the process in which the external pressure is reduced to a pressure at which the blockage of the neck is released, the external pressure becomes a pressure at which the adsorption of the bottle part is released. However, even in this state, the nitrogen adsorbed inside the bottle part due to the blockage of the neck part is retained as it is (the so-called blocking phenomenon). When measuring the desorption isotherm at liquid nitrogen temperature (e.g., 77 K) using nitrogen as the adsorbate, the nitrogen adsorption layer in the neck part starts boiling (cavitation) at a relative pressure higher than the pressure at which the neck part opens. For this reason, the nitrogen adsorbed in the bottle part and the neck part is desorbed and released all at once at the pressure at which the nitrogen adsorption layer starts boiling. When the bottleneck pore constitutes a pore in a carbon particle (a pore in a branch of a dendritic carbon nanostructure), this pressure is the relative pressure P / P 0 It is known that the relative pressure P / P is around 0.4. 0 is the relative pressure specific to nitrogen adsorption that does not depend on the pore structure of the adsorbate. In other words, the relative pressure P / P at which the second hysteresis loop A2 closes is 0 (i.e., the pressure at which cavitation begins) does not depend on the pore structure, but is determined by the adsorbate (nitrogen molecules) and the measurement temperature. Therefore, in this disclosure, the presence of bottleneck pores and the size of the volume of the bottle part are determined from the amount of nitrogen desorbed and released by cavitation. In this disclosure, the number of bottleneck pores is reduced, and even if bottleneck pores are present, the volume of the bottle part is reduced. The phenomenon of hysteresis is explained in detail, for example, in the following document.

[0039] (Literature): Adsorption Hysteresis of Nitrogen and Argon in Pore Networks and Characterization of Novel Micro- and Mesoporous Silicas, Langmuir 2006, 22, 756-764

[0040] As is clear from Fig. 2, the diameter of the neck portion 30B is smaller than the diameter of the bottle portion 30A, so gas does not easily flow into the bottle portion 30A. Also, gas inside the bottle portion 30A does not easily flow out to the outside. Therefore, it can be said that the greater the ratio of the volume of the bottleneck pores to the volume of all pores in the catalyst carrier, the higher the gas diffusion resistance.

[0041] The volume ratio of the bottleneck pores corresponds to the area of ​​the hysteresis loop, i.e., the smaller the area of ​​the hysteresis loop, the smaller the volume ratio of the bottleneck pores.

[0042] As mentioned above, in order to reduce the overvoltage during large current flow, it is important to increase the pore size between the branches of the dendritic carbon nanostructure and to increase the pore volume. This can be expressed as the hysteresis loop of nitrogen gas adsorption as follows:

[0043] "Large pore size" corresponds to the adsorption curve rising in a region of high relative pressure. Specifically, in the BJH (Barrett-Joyner-Halender) analysis, a relative pressure of 0.87 corresponds to a diameter of 20 nm, a relative pressure of 0.95 corresponds to a diameter of 38 nm, a relative pressure of 0.97 corresponds to a diameter of 64 nm, and a relative pressure of 0.98 corresponds to a diameter of 93 nm. In the case where the carbon material for catalyst carrier of the present disclosure is a dendritic carbon nanostructure, the branch diameter is, for example, approximately 50 nm to 100 nm, so the relative pressure at which adsorption rises is 0.97 to 0.98. Furthermore, since the branch diameters are uniform, the rise of adsorption is steep. For example, Ketjen Black EC300, which is a typical porous carbon of carbon black with a dendritic structure, has a particle diameter of around 40 nm, and adsorption rises at a relative pressure of around 0.95, and since there is variation in the pore diameter, the slope of adsorption is smaller than that of the dendritic carbon nanostructure. On the other hand, "large pore volume" corresponds to the amount of gas adsorption. Specifically, when the carbon material for catalyst support of the present disclosure is a dendritic carbon nanostructure, the adsorption between the branches corresponds to the amount of adsorption at a relative pressure of 0.95 to 0.99. By correlating this value with the large current characteristics, the present inventors have succeeded in quantitatively defining the structure corresponding to the gap between the branches in the present disclosure.

[0044] In addition, in the present disclosure, it is preferable that the areas of the first hysteresis loop A1 and the second hysteresis loop A2 are small. As described above, in the present disclosure, the inter-branch pores are multiply branched between the branches, and have a relatively thick, cylindrical shape. Similarly, the intra-branch pores are multiply branched within the branches, and have a relatively thick, cylindrical shape. For this reason, there are almost no bottleneck pores between the branches and within the branches, and as a result, the areas of the first hysteresis loop A1 and the second hysteresis loop A2 are small. Furthermore, since the inter-branch pores are relatively thick, the first hysteresis loop A1 has a relatively high relative pressure P / P 0 Close with.

[0045] The first hysteresis loop A1 and the second hysteresis loop A2 are characteristically observed in the nitrogen adsorption / desorption isotherm of the dendritic carbon nanostructure as the carbon material for a catalyst support according to the present disclosure. Two hysteresis loops are not observed in the nitrogen adsorption / desorption isotherm of other conventional carbon materials. Therefore, the pore structure specific to the dendritic carbon nanostructure according to the present disclosure can be evaluated based on the nitrogen adsorption / desorption isotherm.

[0046] As described above, in the dendritic carbon nanostructure of the present disclosure, the intra-branch pores have a thick, long, cylindrical shape and are branched in various ways within the branches. In order to further reduce the overvoltage during large currents, it is preferable to enlarge the intra-branch pores and increase the branching of the intra-branch pores. Enlarging the intra-branch pores is reflected in the second hysteresis loop A2. Specifically, the area of ​​the second hysteresis loop A2 is reduced because the diffusibility of gas within the pores is improved.

[0047] Furthermore, in dendritic carbon nanostructures, the inter-branch pores have a thick, long, cylindrical shape, and are branched in various ways between the branches. In order to further reduce the overvoltage during large currents, it is preferable to thin the branches. Furthermore, it is preferable that the distribution of branch diameters is sharp. This makes it easier for gas to flow through the inter-branch pores. Enlarging the inter-branch pores and sharpening the distribution of branch diameters is reflected in the first hysteresis loop A1. Specifically, the distribution of the diameters of the inter-branch pores becomes narrower and is concentrated on the longer diameter side, so that in the nitrogen adsorption isotherm, the relative pressure P / P 0 = 0.99 adsorption amount and relative pressure P / P 0 = 0.95 and the difference in adsorption amount △V 0.95-0.99 becomes larger.

[0048] The present inventors have studied a method for producing a dendritic carbon nanostructure that satisfies the above requirements. In general, the dendritic carbon nanostructure is produced by ejecting metal from a metal acetylide. Here, the metal acetylide is produced by adding acetylene to a metal salt solution while irradiating the metal salt solution with ultrasonic waves. In this process, a nucleus of the metal acetylide is generated in the solution, and the metal acetylide grows from this nucleus. The metal salt solution is produced by dissolving a metal salt in an aqueous ammonia solution. Therefore, in order to reduce the concentration of the nucleus of the metal acetylide generated in the metal salt solution, the present inventors have significantly diluted the concentration of the metal salt compared to the conventional process and increased the concentration ratio of ammonia to the anion component of the metal salt. Furthermore, in order to slow down the generation (growth) reaction of the metal acetylide, the addition rate of acetylene is reduced. Furthermore, in order to slow down the generation reaction of the metal acetylide, the concentration of the dissolved acetylene gas is reduced. Specifically, the metal salt solution was kept warm, i.e., the temperature was kept high during the reaction to produce the metal acetylide.

[0049] Furthermore, the present inventors decided to eject metal from the metal acetylide after compression molding the metal acetylide. That is, by heating the metal acetylide, the metal acetylide undergoes an explosive self-decomposition reaction, and the metal is ejected from the metal acetylide. This produces an intermediate (hereinafter also referred to as a "carbon nano intermediate") that is a mixture of a metal layer and a carbon layer. Therefore, the present inventors decided to make it difficult for reaction heat to escape from the metal acetylide by compression molding the metal acetylide. This allows reaction heat to be efficiently supplied to the unreacted portion of the metal acetylide. That is, the reaction heat of the metal acetylide itself is unchanged in principle. Therefore, by making it difficult for such reaction heat to escape to the outside, the amount of heat supplied to the unreacted portion of the metal acetylide is relatively increased, and the temperature of the metal acetylide is smoothly raised. Furthermore, the present inventors decided to increase the temperature rise rate of the metal acetylide in order to further smooth the temperature rise of the metal acetylide. This was intended to promote the reaction of the metal acetylide.

[0050] As a result, in the final product, the dendritic carbon nanostructure, the pores in the branches were made thicker and the branching of the pores in the branches was improved. Specifically, the area △S of the second hysteresis loop A2 0.4-0.87 The P / P ratio was increased to 5mL / g to 50mL / g. Furthermore, the branches were thinned while maintaining the dendritic structure. The branch diameter distribution was also narrowed. 0 = 0.99 adsorption amount and P / P 0 = 0.95 and the difference in adsorption amount △V 0.95-0.99 The density of the branches was reduced while the dendritic structure of the dendritic carbon nanostructures was maintained, as confirmed by scanning electron microscope (SEM).

[0051] Furthermore, the inventors have improved the durability of the dendritic carbon nanostructure by treating the dendritic carbon nanostructure at high temperature. Based on the above findings, the inventors have obtained a carbon material for a catalyst support according to the present disclosure.

[0052] In the present disclosure, "exhibiting two hysteresis loops" refers to the presence of two closed hysteresis loops. The state in which the hysteresis loops are closed indicates that the value obtained by subtracting the adsorption amount (ΔV) indicated by the adsorption isotherm from the adsorption amount indicated by the desorption isotherm at the start and end points of the hysteresis loop is 20 mL / g or less.

[0053] Moreover, the term "exhibiting two hysteresis loops" includes the following aspects. (1) An embodiment in which the end point of the first hysteresis loop is the same as the start point of the second hysteresis loop, that is, the relative pressures of the end point of the first hysteresis loop and the start point of the second hysteresis loop are the same. (2) An embodiment in which the end point of the first hysteresis loop and the start point of the second hysteresis loop are separated from each other, that is, the relative pressures of the end point of the first hysteresis loop and the start point of the second hysteresis loop are different.

[0054] The carbon material for a catalyst carrier according to the present disclosure has two hysteresis loops, one for the relative pressure P / P 0 The first hysteresis loop exists in the range of 0.87 or more, and the relative pressure P / P 0 It is preferable that the second hysteresis loop exists within a range of 0.4 to 0.87. When two hysteresis loops exist in this range, the overvoltage at the time of a large current is likely to be reduced. In the same respect, it is more preferable that the carbon material for a catalyst support according to the present disclosure satisfies the following requirements.

[0055] A more preferred embodiment of the carbon material for a catalyst support according to the present disclosure satisfies the following requirements (A), (B), and (C): In the present disclosure, the nitrogen adsorption / desorption isotherm is measured at liquid nitrogen temperature (e.g., 77 K). (A) BET analysis of nitrogen adsorption isotherm shows a specific surface area of ​​450 m 2 / g~1500m 2 / g. (B) Nitrogen adsorption / desorption isotherm at relative pressure P / P 0 A first hysteresis loop is formed in a range of 0.87 or more, and the relative pressure P / P 0The difference in the amount of adsorption in the first hysteresis loop, △V, is within the range of 0.87±0.03. 0.87 The minimum value of △V 0.87min is less than 20 mL / g. (C) Nitrogen adsorption / desorption isotherm at relative pressure P / P 0 A second hysteresis loop is formed within the range of 0.4 to 0.87, and the area of ​​the second hysteresis loop △S 0.4-0.87 is 5-50mL / g.

[0056] (1-1.Requirement (A)) The specific surface area based on the BET analysis of the nitrogen adsorption isotherm is 450 m 2 / g~1500m 2 / g. This allows more catalyst components to be supported. 2 If the BET specific surface area is less than 1500 m / g, the supportability of the catalyst component may decrease. 2 When the BET specific surface area exceeds 500 m / g, it may be difficult to achieve both the physical strength and the resistance to oxidation and wear of the carbon material for a catalyst support. 2 / g or more, and the preferred upper limit of the BET specific surface area is 1450 m 2 The BET specific surface area may be measured by the method described in the Examples below.

[0057] (1-2.Requirement (B)) Nitrogen adsorption / desorption isotherm is a function of relative pressure P / P 0 A first hysteresis loop is shown in the range of 0.87 or more, and the relative pressure P / P 0 The difference in the amount of adsorption in the first hysteresis loop, △V, is within the range of 0.87±0.03. 0.87 The minimum value of △V 0.87min is 20mL / g or less. 0.87 can be measured by the method described in the Examples below.

[0058] Relative pressure P / P 0 The difference in the amount of adsorption in the first hysteresis loop, △V, is within the range of 0.87±0.03. 0.87 The minimum value of △V0.87min The first hysteresis loop is the relative pressure P / P 0 This means that the difference in the amount of adsorption in the first hysteresis loop, ΔV 0.87 is the value obtained by subtracting the adsorption amount shown by the adsorption isotherm from the adsorption amount shown by the desorption isotherm. 0.87 The minimum value of △V 0.87min is the relative pressure P / P 0 is within the range of 0.87±0.03 and is 20mL / g or less. In other words, △V 0.87 The minimum value of △V 0.87min In Figure 1, the relative pressure P / P 0 When is 0.87, the adsorption amount difference △V 0.87 is the smallest (see Figure 1).

[0059] (1-3. Requirement (C)) The nitrogen adsorption / desorption isotherm at liquid nitrogen temperature is expressed as the relative pressure P / P 0 A second hysteresis loop is shown in the range of 0.4 to 0.87, and the area of ​​the second hysteresis loop △S 0.4-0.87 is 5mL / g to 50mL / g (see Figure 1). 0.4-0.87 The preferred lower limit of is 7 mL / g or more, and △S 0.4-0.87 The preferred upper limit of ΔS is 45 mL / g or less. 0.4-0.87 can be measured by the method described in the Examples below.

[0060] In conventional dendritic carbon nanostructures, the intra-branch pores also have a thick, long, cylindrical shape, and are branched in various ways within the branches. In the carbon material for catalyst supports according to the present disclosure, the characteristics of the inter-branch pores are maintained, while the intra-branch pores are made thicker, and the branching of the intra-branch pores is further enhanced. As a result, the second hysteresis loop is very small. Specifically, the area ΔS of the second hysteresis loop 0.4-0.87 is 5 to 50 mL / g. This reduces the gas diffusion resistance and the overvoltage at high currents. The area of ​​the second hysteresis loop, △S 0.4-0.87When the flow rate is 50 mL / g or less, the volume of the bottleneck pores in the total volume of the pores in the branches decreases. This leads to a favorable reduction in the gas diffusion resistance. The area of ​​the second hysteresis loop, △S 0.4-0.87 When the conductivity is 5 mL / g or more, the decrease in strength of the carbon material for a catalyst support is suppressed, and as a result, the overvoltage during a large current flow is reduced, which is preferable.

[0061] (1-4.Requirement (D)) In addition to the requirements (A) to (C), the carbon material for a catalyst support preferably further satisfies the following requirement (D). Requirement (D) is that in a nitrogen adsorption isotherm, 0 Amount of adsorption at P / P = 0.99 and relative pressure 0 Difference in adsorption amount between the adsorption amount at V = 0.95 and the adsorption amount at V 0.95-0.99 is 500mL / g to 1100mL / g (see Figure 1). 0.95-0.99 The preferred lower limit of is 550 mL / g or more, and △V 0.95-0.99 The preferred upper limit of ΔS is 950 mL / g or less. 0.4-0.87 can be measured by the method described in the Examples below.

[0062] As described above, in a dendritic carbon nanostructure, the inter-branch pores have a thick, long, cylindrical shape, and are branched in various ways between the branches. In the carbon material for catalyst supports according to the present disclosure, the inter-branch pores are made thicker while maintaining the characteristics of the inter-branch pores, and the variation in diameter is also reduced. Therefore, in the nitrogen adsorption isotherm, the relative pressure P / P 0 = 0.99 adsorption amount and relative pressure P / P 0 = 0.95 and the difference in adsorption amount △V 0.95-0.99 In other words, the distribution of the diameters of the inter-branch pores becomes more concentrated on the longer side. Specifically, the adsorption amount difference △V 0.95-0.99 The difference in adsorption amount, △V, is 500mL / g to 1100mL / g. This reduces the gas diffusion resistance and the overvoltage at high current. 0.95-0.99 When the adsorption rate is 500 mL / g or more, the distribution of the diameters of the inter-branch pores becomes narrow and the diffusion resistance is sufficiently reduced. 0.95-0.99It is extremely difficult to prepare a carbon material for a catalyst support with a molecular weight exceeding 1100 mL / g.

[0063] (1-5.Requirements (E)) The carbon material for the catalyst support must satisfy requirements (A) to (C) or requirements (A) to (D) and, in addition, must have a Raman spectroscopic characteristic of 1500 cm -1 ~1700cm -1 The half-width of the G band detected in the range is 45 cm -1 ~70cm -1 It is preferable that the carbon material for a catalyst support further satisfies the requirement (E) that the catalyst support carbon material has a high resistance to oxidation and a high durability. In other words, even if a polymer electrolyte fuel cell using the carbon material for a catalyst support is repeatedly started and stopped, the carbon material for a catalyst support is less susceptible to oxidation and consumption.

[0064] Here, the half-width of the G band is 45 cm -1 ~70cm -1 In this case, the degree of graphitization (crystallinity) of the carbon material for catalyst carriers is improved. Therefore, the oxidation resistance is improved. -1 If the half-width of the G band is more than 45 cm, the oxidation resistance of the carbon material for the catalyst support decreases, and as a result, the overvoltage at high currents increases. -1 If the width is less than 48 cm, the shape of the intrabranch pores and interbranch pores is likely to be maintained, and as a result, the requirements (B) and (C) may not be satisfied. -1 The preferred upper limit is 68 cm. -1 The half width of the G band may be measured by the method described in the Examples below.

[0065] <2. Method for producing carbon material for catalyst support> Next, an example of a preferred method for producing a carbon material for a catalyst support will be described. According to the preferred method for producing a carbon material for a catalyst support, the nitrogen adsorption isotherm shows two hysteresis loops in a range of a relative pressure of 0.4 or more, and furthermore, the requirements (A) to (E) can be satisfied. An example of a preferred method for producing a carbon material for a catalyst support includes a metal acetylide production step, a first heat treatment step, and a second heat treatment step. Furthermore, a cleaning step may be included between the first heat treatment step and the second heat treatment step.

[0066] (2-1. Metal acetylide generation process) In this process, metal acetylides are produced by adding acetylene to a metal salt solution while irradiating it with ultrasonic waves, which produces a precipitate of the metal acetylide (e.g., silver acetylide, copper acetylide, etc.) in the metal salt solution.

[0067] Here, examples of the metal salt include silver nitrate and cuprous chloride. Among these, silver nitrate is preferred. The metal salt solution is obtained by dissolving the metal salt in an aqueous ammonia solution. Examples of the method of adding acetylene include a method of blowing acetylene gas into the metal salt solution. Ultrasonic irradiation can be performed using, for example, an ultrasonic vibrator or an ultrasonic cleaner. It is also preferable to replace oxygen in the metal salt solution with an inert gas before adding acetylene gas. This is to suppress unintended explosive decomposition reaction of the metal acetylide. The time for blowing the inert gas into the metal salt solution may be about 40 to 60 minutes. Examples of the inert gas include argon and nitrogen.

[0068] In addition, in the present disclosure, in order to reduce the concentration of the metal acetylide nuclei generated in the metal salt solution, the metal salt concentration is significantly diluted compared to conventional processes, and the concentration ratio of ammonia to the anion component of the metal salt is increased. The specific metal salt concentration varies depending on the metal species used, and can be determined by experiment. The same applies to the ammonia concentration ratio. In other words, when the metal salt concentration is high or the ammonia concentration ratio is low, the requirement (B) cannot be met, and further, it becomes difficult to meet any of the requirements (A), (C), and (D).

[0069] For example, when the metal salt is silver nitrate, the concentration of the metal salt is 0.1 mass% to less than 5 mass% with respect to the mass of the metal salt solution. The upper limit of the metal salt concentration is preferably 2 mass% or less. Furthermore, the concentration ratio of ammonia to the anion component of the metal salt is 1 or more, preferably 3 or more. This makes it possible to prepare a carbon material for a catalyst support that satisfies the above-mentioned requirements (A) to (D). When the concentration of the metal salt is 0.1 mass% or more, the strength of the carbon material for a catalyst support, which is the final product, is ensured. On the other hand, when the concentration of the metal salt is less than 5 mass% or the concentration ratio of ammonia to the anion component of the metal salt is 1 or more, the concentration of the nuclei of the metal acetylide generated in the metal salt solution becomes appropriate. As a result, the adsorption amount difference ΔV 0.95-0.99 The relative pressure P / P 0 = It becomes easier to close around 0.87.

[0070] Furthermore, in the present disclosure, the acetylene addition rate is slowed down to allow the metal acetylide generation (growth) reaction to proceed slowly. Specifically, for example, acetylene gas is slowly blown into the metal salt solution. The specific blowing flow rate varies depending on the type of metal used, and may be determined by experiment. In other words, if the acetylene blowing flow rate is high, requirement (B) cannot be satisfied, and furthermore, any of requirements (A), (C) and (D) will not be satisfied. For example, if the metal salt becomes silver nitrate, the upper limit of the acetylene gas blowing flow rate is less than 20 mL / min. The acetylene gas blowing flow rate is preferably 15 mL / min or less, and more preferably 10 mL / min or less. If the acetylene gas blowing rate is less than 20 mL / min, the area ΔS of the second hysteresis loop will be 0.4-0.87 is 50 mL / g or less. In other words, the thickness and branching of the pores in the branches are sufficient. The volume of the bottleneck pores in the total volume of the pores in the branches is reduced. Furthermore, the first hysteresis loop is likely to close at a relative pressure of about 0.87. The lower limit of the flow rate of the acetylene gas blowing is not particularly limited, and may be 0.5 mL / min or more.

[0071] Furthermore, in the present disclosure, the metal salt solution is kept warm in order to reduce the concentration of dissolved acetylene gas and slow the reaction rate of the metal acetylide. The specific temperature varies depending on the type of metal used, and can be determined by experiment. In other words, if the temperature is high, requirement (B) cannot be met, and furthermore, any of requirements (A), (C) and (D) will not be met. For example, if the metal salt becomes silver nitrate, the metal salt solution is kept warm at a temperature above 10°C. The temperature of the metal salt solution is preferably 20°C or higher, and more preferably 60°C or higher. If the temperature of the metal salt solution exceeds 10°C, the adsorption amount difference ΔV 0.95-0.99 is 500mL / g to 1100mL / g. In other words, the distribution of the diameter of the interbranch pores becomes narrower, and the gas diffusion resistance becomes lower. Furthermore, the area of ​​the second hysteresis loop, △S 0.4-0.87is 50 mL / g or less. In other words, the thickness and branching of the pores in the branches are sufficient. In addition, the volume of the bottleneck pores in the total volume of the pores in the branches decreases, and the first hysteresis loop tends to close at a relative pressure of about 0.87. The upper limit of the temperature is not particularly limited, and may be 70°C or less.

[0072] (2-2. First Heat Treatment Step) In the first heat treatment step, the metal acetylide is heated to eject the metal from the metal acetylide. Here, in the present disclosure, the metal acetylide is compression molded and then heated. That is, by heating the metal acetylide, the metal acetylide undergoes an explosive self-decomposition reaction, and the metal is ejected from the metal acetylide. This produces a carbon nano intermediate. In the present disclosure, the metal acetylide is compression molded, so that reaction heat is less likely to escape from the metal acetylide. This allows reaction heat to be efficiently supplied to the unreacted portion of the metal acetylide. In other words, the reaction heat of the metal acetylide itself is unchanged in principle. Therefore, in the present disclosure, by making it difficult for such reaction heat to escape to the outside, the amount of heat supplied to the unreacted portion of the metal acetylide is relatively increased, and the temperature of the metal acetylide is smoothly increased. In the present disclosure, in order to further smooth the temperature increase of the metal acetylide, the temperature increase rate of the metal acetylide is increased. That is, in the present disclosure, the reaction of the metal acetylide is promoted by carrying out these treatments.

[0073] Here, the molding pressure during compression molding may vary depending on the metal species constituting the metal acetylide, and may be determined by experiment. In other words, if the molding pressure is insufficient, reaction heat cannot be efficiently supplied to the unreacted portion of the metal acetylide. As a result, requirement (B) cannot be satisfied, and further, any of requirements (A), (C), and (D) is not satisfied. For example, when the metal acetylide becomes silver acetylide, the molding pressure is 0.5 kg / cm. 2 This allows efficient supply of reaction heat to the unreacted portion of the metal acetylide. The molding pressure is preferably 1.0 kg / cm 2 More preferably, it is 2.0 kg / cm 2More preferably, it is 2.5 kg / cm 2 That's all. The molding pressure is 0.5kg / cm 2 When the molding pressure is greater than 0.87, it becomes possible to efficiently supply reaction heat to the unreacted portion of the metal acetylide. In addition, the first hysteresis loop tends to close at a relative pressure of about 0.87. There is no particular upper limit to the molding pressure, and it is 3 kg / cm. 2 It may be the following.

[0074] In addition, the heating rate may vary depending on the metal species constituting the metal acetylide, so it may be specified by experiment. That is, when the heating rate is low, reaction heat cannot be efficiently supplied to the unreacted portion of the metal acetylide. As a result, requirement (B) cannot be satisfied, and further, any of requirements (A), (C) and (D) is not satisfied. For example, when the metal acetylide becomes silver acetylide, the heating rate is greater than 2°C / min. The heating rate is preferably 5°C / min or more, more preferably 100°C / min or more. When the heating rate exceeds 2°C / min, it becomes possible to efficiently supply reaction heat to the unreacted portion of the metal acetylide. As a result, for example, requirement (C) can be satisfied. The upper limit of the heating rate is not particularly limited, and may be 300°C / min or less.

[0075] The holding temperature after heating also differs depending on the metal species constituting the metal acetylide. For example, when silver acetylide is heated, the holding temperature may be 160°C to 200°C. When copper acetylide is heated, the holding temperature may be 210°C to 250°C.

[0076] (2-3. Cleaning process) In the washing process, metal components are removed from the carbon nano intermediate to produce a carbon material for a catalyst support. Specifically, for example, the carbon nano intermediate is washed with nitric acid (or an aqueous solution of nitric acid). As a result, the metal components and unstable carbon compounds in the carbon nano intermediate are dissolved in the aqueous solution of nitric acid. This makes it possible to remove not only the metal components but also the unstable carbon compounds from the carbon nano intermediate. Note that this process turns the areas where the metal components were present into voids, so that the carbon material for a catalyst support has a three-dimensional structure with a large specific surface area.

[0077] (2-4. Second Heat Treatment Step) In the second heat treatment step, the carbon material for catalyst support is heated at 1400°C to 2500°C in a vacuum or in an inert gas atmosphere. The heating temperature is preferably 1600°C to 2100°C. If the heating temperature in this second heating step is 1400°C or higher, the crystallinity of the carbon material for catalyst support is improved, and durability in a fuel cell usage environment is more easily ensured. As a result, requirement (E) is more easily met. Furthermore, if the heating temperature is 2500°C or lower, the shapes of the intra-branch pores and inter-branch pores are more easily maintained. As a result, requirements (B) and (C) are more easily met. From the viewpoint of increasing the durability of the carbon material for catalyst support, it is preferable to carry out the second heat treatment.

[0078] The heat treatment time also affects the properties of the carbon material for catalyst carriers. The heat treatment time may be 20 to 200 minutes. The heat treatment time is considered to be related to the uniformity of crystallinity. If the heat treatment time is too short, the crystallinity of only the outer surface of the carbon material increases, while the crystallinity of the inside may not develop sufficiently, which may lead to a decrease in durability. If the heat treatment time is 20 minutes or more, the crystallinity of the inside improves. On the other hand, if the heat treatment time is too long, it leads to a decrease in industrial productivity. As long as the heat treatment time is 200 minutes or less, any carbon material can be uniformly crystallized to the inside.

[0079] Here, the heating method of the carbon material for a catalyst support is not particularly limited as long as it can heat the carbon material for a catalyst support to the above temperature. Examples of the heating method include resistance heating, microwave heating, high frequency heating, and furnace-type heating methods. Examples of the furnace type include a batch furnace and a tunnel furnace. There is no limitation on the furnace type as long as it can achieve an inert or reduced pressure atmosphere.

[0080] As described above, the carbon material for catalyst supports according to the present disclosure satisfies the requirements (A) to (C) by the above-mentioned preferred production method. In addition, by selecting preferred conditions, the carbon material for catalyst supports further satisfies at least one of the requirements (D) and (E). Therefore, by using this carbon material for catalyst supports as a catalyst support for a polymer electrolyte fuel cell, the gas diffusion resistance in the catalyst layer is reduced, and the overvoltage during large current is reduced.

[0081] <3. Catalyst layer for polymer electrolyte fuel cell and polymer electrolyte fuel cell> A polymer electrolyte fuel cell will be described together with a catalyst layer for a polymer electrolyte fuel cell. The carbon material for a catalyst support of the present disclosure can be applied to catalyst layers 150 and 160 provided in a polymer electrolyte fuel cell 100 shown in FIG. 3, for example. FIG. 3 is a schematic diagram showing an example of a schematic configuration of a fuel cell according to the present disclosure. The polymer electrolyte fuel cell 100 includes separators 110 and 120, gas diffusion layers 130 and 140, catalyst layers 150 and 160, and an electrolyte membrane 170.

[0082] Separator 110 is an anode-side separator that introduces a reducing gas such as hydrogen into gas diffusion layer 130. Separator 120 is a cathode-side separator that introduces an oxidizing gas such as oxygen gas or air into the gas diffusion condensation phase. The type of separators 110 and 120 is not particularly limited, and may be any separator used in conventional fuel cells (e.g., solid polymer fuel cells).

[0083] The gas diffusion layer 130 is an anode-side gas diffusion layer, which diffuses the reducing gas supplied from the separator 110 and then supplies it to the catalyst layer 150. The gas diffusion layer 140 is a cathode-side gas diffusion layer, which diffuses the oxidizing gas supplied from the separator 120 and then supplies it to the catalyst layer 160. The type of the gas diffusion layers 130 and 140 is not particularly limited, and may be any gas diffusion layer used in conventional fuel cells (e.g., solid polymer fuel cells). Examples of the gas diffusion layers 130 and 140 include porous carbon materials (carbon cloth, carbon paper, etc.), porous metal materials (metal mesh, metal wool, etc.), etc. A preferred example of the gas diffusion layers 130 and 140 is a gas diffusion layer with a two-layer structure. Specifically, the gas diffusion layers 130 and 140 have a two-layer structure in which the layer on the separator 110 or 120 side is a gas diffusion fiber layer mainly composed of a fibrous carbon material, and the layer on the catalyst layer 150 or 160 side is a micropore layer mainly composed of carbon black.

[0084] The catalyst layer 150 is a so-called anode. In the catalyst layer 150, an oxidation reaction of the reducing gas occurs, and protons and electrons are generated. For example, when the reducing gas becomes hydrogen gas, the following oxidation reaction occurs. H 2 →2H + +2e - (E 0 =0V)

[0085] Protons produced by the oxidation reaction reach the catalyst layer 160 through the catalyst layer 150 and the electrolyte membrane 170. Electrons produced by the oxidation reaction reach the external circuit through the catalyst layer 150, the gas diffusion layer 130, and the separator 110. The electrons perform work (power generation) in the external circuit and are then introduced into the separator 120. The electrons then reach the catalyst layer 160 through the separator 120 and the gas diffusion layer 140.

[0086] The configuration of the catalyst layer 150 that serves as the anode is not particularly limited. The configuration of the catalyst layer 150 may be the same as that of a conventional anode, may be the same as that of the catalyst layer 160, or may be more hydrophilic than the catalyst layer 160.

[0087] The catalyst layer 160 is a so-called cathode. In the catalyst layer 160, a reduction reaction of the oxidizing gas occurs, and water is produced. For example, when the oxidizing gas becomes oxygen gas or air, the following reduction reaction occurs. The water produced by the oxidation reaction is discharged to the outside of the polymer electrolyte fuel cell 100 together with the unreacted oxidizing gas. O 2 +4H + +4e - →2H 2 O (E 0 =1.23V)

[0088] In this way, the energy difference (potential difference) between the oxidation reaction and the reduction reaction is utilized to generate electricity in the polymer electrolyte fuel cell 100. In other words, the electrons generated in the oxidation reaction perform work in an external circuit.

[0089] The catalyst layer 160 preferably contains the carbon material for a catalyst support according to the present disclosure. That is, the catalyst layer 160 contains the carbon material for a catalyst support according to the present disclosure, an electrolyte material, and a catalyst component. This can increase the catalyst utilization rate in the catalyst layer 160. And, the catalyst utilization rate of the solid polymer electrolyte fuel cell 100 can be increased.

[0090] The catalyst carrying rate in the catalyst layer 160 is not particularly limited, and is preferably 30% by mass or more and less than 80% by mass. When the catalyst carrying rate is in this range, the catalyst utilization rate is further increased. Here, the catalyst carrying rate is expressed as the mass % of the catalyst component relative to the total mass of the catalyst carrying particles (particles in which the catalyst component is carried on a carbon material for a catalyst carrier). When the catalyst carrying rate is less than 30% by mass, it may be necessary to thicken the catalyst layer 160 in order to make the polymer electrolyte fuel cell 100 practical. On the other hand, when the catalyst carrying rate is 80% by mass or more, catalyst aggregation is likely to occur. In addition, the catalyst layer 160 may become too thin, which may cause flooding.

[0091] The mass ratio I / C of the mass I of the electrolyte material in the catalyst layer 160 to the mass C of the carbon material for the catalyst support is not particularly limited, and is preferably greater than 0.5 and less than 5.0. In this case, the pore network and the electrolyte material network can be compatible, and the catalyst utilization rate is high. On the other hand, when the mass ratio I / C is 0.5 or less, the electrolyte material network becomes weak and the proton conduction resistance tends to be high. When the mass ratio I / C is 5.0 or more, the electrolyte material may break the pore network. In either case, the catalyst utilization rate may decrease.

[0092] Furthermore, the thickness of the catalyst layer 160 is not particularly limited, and is preferably more than 5 μm and less than 20 μm. In this case, the oxidizing gas is easily diffused in the catalyst layer 160, and flooding is unlikely to occur. If the thickness of the catalyst layer 160 is 5 μm or less, flooding is likely to occur. If the thickness of the catalyst layer 160 is 20 μm or more, the oxidizing gas is unlikely to diffuse in the catalyst layer 160, and the catalyst components in the vicinity of the electrolyte membrane 170 are unlikely to work. That is, there is a possibility that the catalyst utilization rate will decrease.

[0093] The electrolyte membrane 170 is made of an electrolyte material having proton conductivity. The electrolyte membrane 170 introduces the protons generated in the above oxidation reaction to the catalyst layer 160 (cathode). Here, the type of electrolyte material is not particularly limited, and it may be an electrolyte material used in conventional fuel cells, for example, solid polymer fuel cells. An example of a suitable electrolyte material is an electrolyte resin. An example of the electrolyte resin is a polymer into which a phosphoric acid group, a sulfonic acid group, or the like is introduced. Specifically, for example, a perfluorosulfonic acid polymer, a polymer into which benzenesulfonic acid, or the like is introduced, or the like is included. Of course, the electrolyte material may be another type of electrolyte material. Examples of such electrolyte materials include inorganic electrolyte materials, inorganic-organic hybrid electrolyte materials, and the like. The solid polymer fuel cell 100 may be a fuel cell that operates within a range of room temperature (25°C) to 150°C.

[0094] <4. Manufacturing method of polymer electrolyte fuel cell> The method for manufacturing the polymer electrolyte fuel cell 100 is not particularly limited, and may be the same as the conventional manufacturing method. However, the catalyst carrier is made of the carbon material for catalyst carrier according to the present disclosure. Of the catalyst layers 150 and 160, it is preferable to use the carbon material for catalyst carrier according to the present disclosure for the catalyst carrier of at least the catalyst layer 160 serving as the cathode. Of course, the carbon material for catalyst carrier according to the present disclosure may be used for the catalyst carrier of both the catalyst layer 150 serving as the anode and the catalyst layer 160 serving as the cathode. EXAMPLES

[0095] <1. Measurement method for each parameter> Next, experimental examples of the carbon material for a catalyst support according to the present disclosure will be described. First, the method of measuring each parameter will be described.

[0096] (1-1. Nitrogen adsorption / desorption isotherm measurement method) Approximately 30 mg of sample was weighed out and vacuum dried at 120°C for 2 hours. The sample was then set in an automatic specific surface area measuring device (MicrotrackBell, BELSORP MAX). Nitrogen adsorption and desorption isotherms were then measured at a measurement temperature of 77K (liquid nitrogen temperature) using nitrogen gas as the adsorbate. Relative pressure P / P 0 The BET specific surface area was calculated by BET analysis of the nitrogen adsorption isotherm in the range of 0.05 to 0.15.

[0097] In addition, the relative pressure P / P 0 The number of hysteresis loops that exist in the range of 0.4 or more was counted. Then, the relative pressure P / P 0 The difference in the amount of adsorption in the first hysteresis loop, △V, is within the range of 0.87±0.03. 0.87 Measure the adsorption amount difference △V 0.87 The minimum value of △V 0.87min Furthermore, the relative pressure P / P 0 The area of ​​the second hysteresis loop, △S, is in the range of 0.4 to 0.87. 0.4-0.87 This △V 0.87 Measurement of and △S 0.4-0.87 For the purpose of measurement, P / P 0 The measurement interval of P / P has been shortened. 0 The measurement interval was set to take fixed points at 0.005 intervals. In other words, the P / P 0 The measurement accuracy is 0.005.

[0098] Hysteresis loop area △S 0.4-0.87 The calculation of each relative pressure P / P was performed as follows: 0 At the measurement point, the amount of adsorption V 1 and the amount of adsorption during the desorption process V 2 The difference between ΔV and P / P 0 The value was calculated by multiplying the measurement interval by 0.005. 0 = 0.4 to 0.87, the integrated value for all measurement points is △S 0.4-0.87 was calculated. Similarly, the difference in adsorption amount △V 0.87 is the relative pressure P / P 0was calculated within the range of 0.87 ± 0.03 with an accuracy of 0.005.

[0099] In addition, the relative pressure P / P 0 = 0.99 adsorption amount and relative pressure P / P 0 = 0.95 and the difference in adsorption amount △V 0.95-0.99 The results are summarized in Table 2. In addition, the relative pressure P / P 0 The first hysteresis loop exists in the range of 0.87 or more, and the relative pressure P / P 0 If a second hysteresis loop exists within the range of 0.4 to 0.87, indicate "2" in the "Number of hysteresis loops" column in Table 2. If only one hysteresis loop exists, indicate "1" in the "Number of hysteresis loops" column in Table 2.

[0100] (1-2. Method for Measuring Raman Spectrum) Approximately 3 mg of the sample was weighed out and the Raman spectrum was measured using a laser Raman spectrophotometer (NRS-3100, manufactured by JASCO Corporation). -1 ~1700cm -1 The peaks in the range were extracted and the half-width (△G) of these peaks was measured. The results are summarized in Table 2. -Measurement conditions- Excitation laser: 532 nm, laser power: 10 mW (sample irradiation power: 1.1 mW), microscope arrangement: backscattering, objective lens: ×100 magnification, spot diameter: 1 μm, exposure time: 30 sec, observation wave number: 2000 cm -1 ~300cm -1 , Number of times: 6

[0101] <2. Preparation of carbon material for catalyst support> Carbon materials for catalyst supports E1-1 to E6-8 and C1-1 to C6-2 were produced by carrying out each operation in the following steps.

[0102] (2-1. Metal acetylide generation process) First, silver nitrate was dissolved in an aqueous ammonia solution to prepare a silver nitrate solution. The ammonia concentration in the silver nitrate solution was 2.0% by mass. The specific concentration of silver nitrate is shown in Table 1. In order to investigate the effect of the silver nitrate concentration, the silver nitrate concentration was varied for each carbon material when preparing the catalyst support carbon materials E1-1 to E1-6 and C1-1 to C1-2.

[0103] Next, argon gas was blown into the silver nitrate solution for 60 minutes to replace the oxygen dissolved in the silver nitrate solution with an inert gas. Next, acetylene gas was blown into the silver nitrate solution at a specified flow rate while stirring the silver nitrate solution with a stirrer. The silver nitrate solution was kept at a specified temperature while blowing in the acetylene gas. Specific values ​​for the temperature of the silver nitrate solution and the blowing flow rate of the acetylene gas are shown in Table 1. In order to investigate the effect of the temperature of the silver nitrate solution, the temperature of the silver nitrate solution was varied for each carbon material when preparing the catalyst support carbon materials E2-1 to E2-5 and C2-1. In addition, in order to investigate the effect of the blowing speed of the acetylene gas, the blowing speed was varied for each carbon material when preparing the catalyst support carbon materials E3-1 to E3-5 and C3-1 to C3-2.

[0104] As a result, a white solid of silver acetylide was precipitated in the silver nitrate solution. When the injected acetylene gas started to be released as bubbles in the solution, it was determined that all of the silver nitrate in the silver nitrate solution had reacted with the acetylene gas, and the injection was stopped. Next, the precipitate in the silver nitrate solution was filtered with a membrane filter, and the obtained precipitate was redispersed in methanol. Next, the methanol dispersion of the precipitate was filtered again. The precipitate was taken out into a petri dish and impregnated with a small amount of methanol.

[0105] (2-2. First Heat Treatment Step) Next, about 0.5 g (mass including methanol) of the precipitate impregnated with methanol (i.e., silver acetylide) was weighed out. Next, the weighed precipitate was placed in a stainless steel pellet molding die with a diameter of 5 mm and slowly pressed at a predetermined pressure (molding pressure). In this way, a silver acetylide pellet was produced. The specific molding pressure is shown in Table 1. In order to investigate the effect of molding pressure, the molding pressure was changed for each carbon material when preparing the catalyst support carbon materials E4-1 to E4-4 and C4-1 to C4-3. Note that the molding pressure "none" for the catalyst support carbon material C4-1 means that no compression was performed. For E4-3 to E4-4, in addition to the molding pressure, the silver acetylide synthesis conditions were also changed. Next, the silver acetylide pellets were transferred to a stainless steel cylindrical container having a diameter of about 5 cm, and this cylindrical container was placed in a vacuum heating electric furnace and vacuum dried at 60° C. for about 15 to 30 minutes.

[0106] Next, the silver acetylide in the cylindrical container was heated to 200°C at a predetermined heating rate while it was in that state (i.e., without taking out the silver acetylide from the cylindrical container). During this process, the silver acetylide caused an explosive self-decomposition reaction, and silver was ejected from the silver acetylide. This produced a carbon nano intermediate, which was a mixture of a metal layer and a carbon layer. Specific heating rates are shown in Table 1. Here, in order to investigate the effect of the heating rate, the heating rate was varied for each carbon material when producing the carbon materials E5-1 to E5-6 and C5-1 for catalyst supports.

[0107] (2-3. Cleaning process) The carbon nano intermediate obtained in the first heat treatment step was washed with concentrated nitric acid having a concentration of 60 mass %. This removed the silver particles and other unstable carbon compounds remaining on the surface of the carbon nano intermediate. The carbon material for catalyst support was then washed with water.

[0108] (2-4. Second Heat Treatment Step) The carbon material for catalyst supports washed in the washing process was heated at a specified temperature for two hours to increase the graphitization degree of the carbon material for catalyst supports. The specific heating temperature and heat treatment time are shown in Table 1. Here, in order to show the influence of the heating temperature and the heat treatment time, the combination of the heating temperature and the heat treatment time was changed for each carbon material when producing the catalyst support carbon materials E6-1 to E6-8 and C6-1 to C6-2.

[0109] The carbon materials for catalyst supports E1-1 to E6-8 and C1-1 to C6-2 were produced by the above steps. The physical properties of these carbon materials for catalyst supports are shown in Table 2.

[0110] In addition, Ketjen Black EC600JD (manufactured by Lion Corporation) was prepared as a commercially available carbon material for catalyst supports. EC600JD was also heat-treated at 1800°C for 2 hours under argon flow to prepare EC600JD-1800. These Ketjen Blacks have a dendritic structure similar to dendritic carbon nanostructures, have developed pores within the branches, and have a large BET specific surface area.

[0111] In addition, CNovel-MH (manufactured by Toyo Tanso Co., Ltd.) was prepared. In addition, MH-2000 was prepared by heat-treating CNovel-MH at 2000°C for 2 hours under argon flow. These carbon materials are porous carbon materials that do not have a dendritic structure. These carbon materials have many pores formed in the carbon particles.

[0112] Furthermore, gas diffusion is improved if these pores are connected to each other. For this purpose, MH-2000 was heated in air to oxidize and consume the carbon. Specifically, a horizontal tubular electric furnace was used, and the gas passed through was dry air, and the material was treated at 560°C for 1 hour (this carbon material is referred to as MH-2000-Air560). This air oxidation treatment caused a weight loss of 46% by mass. The area of ​​the hysteresis loop was greatly reduced by this air oxidation treatment. The calculated value of the area of ​​the hysteresis loop for MH-2000 before the air oxidation treatment was 61, while the calculated value of the area of ​​the hysteresis loop for MH-2000-Air560 after the air oxidation treatment was 0.6. That is, the hysteresis loop was substantially eliminated by the air oxidation treatment, and the adsorption and desorption curves almost coincided.

[0113] In addition, Acetylene Black AB (manufactured by Denka Co., Ltd.) and conductive grade #4500 (manufactured by Tokai Carbon Co., Ltd.) were prepared. These carbon materials have a developed dendritic structure, but have almost no pores within the branches. The physical properties of these commercially available carbon materials for catalyst supports are shown in Table 2.

[0114] [Table 1]

[0115] [Table 2]

[0116] <3. Preparation of MEA> Using the catalyst support carbon materials E1-1 to E6-8 and C1-1 to C6-2, and a commercially available catalyst support carbon material, MEAs (membrane electrode assemblies) were produced by the following steps.

[0117] (3-1. Platinum loading treatment) The carbon material for catalyst carrier was dispersed in distilled water to prepare a carbon material dispersion. Then, formaldehyde was added to this carbon material dispersion, and the mixture was placed in a water bath set at 40°C. Then, the mixture was left on standby until the temperature of the carbon material dispersion reached 40°C, the same as that of the bath. Then, while stirring the carbon material dispersion, the dinitrodiamine Pt complex nitric acid aqueous solution was slowly poured into the carbon material dispersion. After stirring for about 2 hours, the carbon material dispersion was filtered, and the obtained solid was washed. The solid thus obtained was vacuum dried at 90°C, and then pulverized in a mortar to obtain a pulverized solid. Then, the pulverized solid was heat-treated at 200°C for 1 hour in an argon atmosphere containing 5% by volume of hydrogen. Thus, a platinum-supported carbon material was prepared.

[0118] The amount of platinum carried in the platinum-supporting carbon material was 40 mass % based on the total mass of the catalyst support carbon material and the platinum particles, and was confirmed by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0119] (3-2. Preparation of coating ink) A Nafion solution in which Nafion (Dupont's Nafion, registered trademark: Nafion, persulfonic acid-based ion exchange resin) was dissolved as the electrolyte resin was prepared. Next, platinum-supported carbon material (Pt catalyst) and the Nafion solution were mixed in an argon atmosphere. Here, the mass ratio of the solid content of the electrolyte resin was 1.0 times that of the platinum-supported carbon material. However, when using non-porous AB or #4500 as the carbon material for the catalyst carrier, the mass ratio of the solid content of the electrolyte resin was 0.5 times. Next, the mixed solution was lightly stirred, and then the platinum-supported carbon material in the mixed solution was crushed by ultrasonic waves. Next, ethanol was further added to the mixed solution, and the total solid content concentration of the platinum-supported carbon material and the electrolyte resin was adjusted to 1.0 mass% with respect to the total mass of the mixed solution. In this way, a coating ink containing a platinum-supported carbon material and an electrolyte resin was prepared.

[0120] (3-3. Preparation of catalyst layer) Next, the mass of platinum per unit area of ​​the catalyst layer (hereinafter referred to as "platinum coverage") is 0.2 mg / cm 2 The spray conditions were adjusted so that the coating ink was sprayed onto a Teflon sheet. A drying process was then performed in an argon atmosphere at 120° C. for 60 minutes to prepare a catalyst layer on the Teflon sheet. Two identical catalyst layers were prepared, one of which was used as the cathode and the other as the anode.

[0121] (3-4. Preparation of MEA) A square electrolyte membrane with sides of 6 cm was cut out from a Nafion membrane (NR211 manufactured by Dupont). The Teflon (registered trademark) sheets on which the anode and cathode catalyst layers were provided were each cut out into a square with sides of 2.5 cm using a cutter knife. The electrolyte membrane was sandwiched between the anode and cathode catalyst layers on the sheets thus cut out, and pressed to form a laminate. Specifically, the electrolyte membrane was sandwiched between the catalyst layers by the center of the electrolyte membrane, and the catalyst layers and the electrolyte membrane were in contact with each other and pressed so that there was no misalignment between them, to obtain a laminate. The pressing was performed at 120°C and 100 kg / cm. 2 The laminate was then cooled to room temperature. The Teflon (registered trademark) sheets were then carefully peeled off from each of the anode and cathode catalyst layers. Through the above steps, the anode and cathode catalyst layers were fixed to the electrolyte membrane.

[0122] Next, two square pieces of carbon paper with sides of 2.5 cm were cut out from the carbon paper (35BC manufactured by SGL Carbon Co., Ltd.) that would become the gas diffusion layers. These cut-out carbon papers were then laminated with the catalyst layers of the anode and cathode without causing any misalignment to produce a laminate. The laminate was then heated at 120°C and 50 kg / cm 2The MEA was fabricated by pressing for 10 minutes at 100° C. The mass of the catalyst layer fixed to the Nafion membrane was calculated from the difference between the mass of the Teflon® sheet with the catalyst layer before pressing and the mass of the Teflon® sheet peeled off after pressing. The platinum weight, catalyst carrier carbon material weight, and electrolyte resin weight were calculated from the mass ratio of the catalyst layer composition. Using this method, the platinum weight was calculated to be 0.2 mg / cm2. 2 It was confirmed that.

[0123] <4. Performance evaluation test> The fabricated MEAs were each incorporated into a cell, which was then attached to a fuel cell measuring device to evaluate the performance of the fuel cell.

[0124] Air was supplied to the cathode and pure hydrogen to the anode under atmospheric pressure so that the utilization rates were 40% and 70%, respectively. The cell temperature was set to 80°C. The air and pure hydrogen supplied to the fuel cell were humidified by passing them through distilled water kept at 65°C in a humidifier (i.e., bubbling). In other words, these gases were made to contain water vapor equivalent to the reformed hydrogen. The humidified gas was then supplied to the cell. After supplying the gas to the cell under these conditions, the load was gradually increased to 200 mA / cm. 2 , and 1000mA / cm 2 The cell terminal voltage at this point was recorded as the output voltage, and the performance of the fuel cell was evaluated.

[0125] The performance evaluation results of the obtained fuel cells were evaluated according to the voltage at each current density, with a pass rank of A or B and a fail rank of C. For the pass rank, a pass was given a B and a higher performance was given an A. The pass rank criteria are as shown in the ranking classification below. The evaluation results are summarized in Table 3.

[0126] [Rank classification method] -200mA / cm 2 Output voltage at - A: 0.86V or higher. B: 0.84V or more and less than 0.86V. C: Less than B. -1000mA / cm 2 Output voltage at - A: 0.65V or higher B: 0.60V or more and less than 0.65V. C: Less than B.

[0127] [Table 3]

[0128] <5. Evaluation> The carbon materials for catalyst supports that satisfy the requirements of this disclosure all have a low current (200 mA / cm 2 ) and at high current (1000mA / cm 2 ) is high. Therefore, the overvoltage is small. In particular, the overvoltage at a large current is particularly low for the carbon materials for catalyst carriers E2-5, E3-1, E4-3, E4-4, E5-5, E5-6, and E6-2 to E6-4. These carbon materials for catalyst carriers are prepared so that any one of the temperature of the silver nitrate solution, the molding pressure, the rate of temperature rise during the first heat treatment, and the heating temperature during the second heat treatment satisfies a particularly preferable condition. The carbon materials for catalyst carriers E4-1 and E4-2 did not satisfy the requirement (D), but the results were good. Of course, particularly good results can be obtained when all of the requirements (A) to (E) are satisfied.

[0129] In contrast, the nitrogen adsorption / desorption isotherms of the carbon materials C1-1, C1-2, C2-1, C3-1, C3-2, C4-1 to C4-3, C5-1, C6-1, and C6-2 for catalyst carriers did not show two hysteresis loops. Therefore, the overvoltage at high current was high. The nitrogen adsorption / desorption isotherms of the commercially available carbon materials for catalyst carriers did not show two hysteresis loops. The overvoltage at low current was high as well as at high current.

[0130] The symbols used in each drawing are as follows: 100 Polymer electrolyte fuel cell 110, 120 separator 130, 140 Gas diffusion layer 150, 160 catalyst layer 170 Electrolyte membrane

Claims

1. Relative pressure P / P 0 In the range of 0.4 or more, the nitrogen adsorption / desorption isotherm shows two hysteresis loops having a first hysteresis loop and a second hysteresis loop, The two hysteresis loops exhibited by the nitrogen adsorption / desorption isotherm include a first hysteresis loop in which the relative pressure P / P 0 is in a range of 0.87 or more, and a second hysteresis loop in which the relative pressure P / P 0 is in a range of 0.4 to 0.87, A carbon material for a catalyst support for a polymer electrolyte fuel cell, which satisfies the following requirements (A), (B), (C) and (D): (A) The specific surface area as determined by BET analysis of the nitrogen adsorption isotherm is 450 m 2 / g to 1500 m 2 / g. (B) In the first hysteresis loop, the minimum value ΔV 0.87min of the adsorption amount difference ΔV 0.87 is 20 mL / g or less within the relative pressure P / P 0 range of 0.87±0.

03. (C) The area ΔS 0.4-0.87 of the second hysteresis loop is 5 mL / g to 50 mL / g. (D) In ​​the nitrogen adsorption isotherm, the adsorption amount difference ΔV 0.95-0.99 between the adsorption amount when the relative pressure P / P 0 is 0.99 and the adsorption amount when the relative pressure P / P 0 is 0.95 is 500 mL / g to 1100 mL / g. Carbon material for catalyst supports in polymer electrolyte fuel cells.

2. In a range where the relative pressure P / P 0 is 0.4 or more, the nitrogen adsorption / desorption isotherm shows two hysteresis loops having a first hysteresis loop and a second hysteresis loop; The two hysteresis loops shown by the nitrogen adsorption / desorption isotherm are the relative pressure P / P 0 A first hysteresis loop in which the relative pressure P / P 0 has a second hysteresis loop that is in the range of 0.4 to 0.87; A carbon material for a catalyst support for a polymer electrolyte fuel cell, which satisfies the following requirements (A), (B), (C) and (E): (A) The specific surface area as determined by BET analysis of the nitrogen adsorption isotherm is 450 m 2 / g to 1500 m 2 / g. (B) In the first hysteresis loop, the minimum value ΔV 0.87min of the adsorption amount difference ΔV 0.87 is 20 mL / g or less within the relative pressure P / P 0 range of 0.87±0.

03. (C) The area ΔS 0.4-0.87 of the second hysteresis loop is 5 mL / g to 50 mL / g. (E) In a Raman spectrum obtained by Raman spectrometry, the half width of the G band detected in the range of 1500 cm -1 to 1700 cm -1 is 45 cm -1 to 70 cm -1 .

3. The carbon material for a polymer electrolyte fuel cell catalyst support according to claim 2 , further satisfying the following requirement (D): (D) In ​​the nitrogen adsorption isotherm, the relative pressure P / P 0 The amount of adsorption at 0.99 and the relative pressure P / P 0 The difference in adsorption amount between the adsorption amount at 0.95 and that at 0.95 is ΔV 0.95-0.99 is 500 mL / g to 1100 mL / g.

4. A catalyst layer for a polymer electrolyte fuel cell, comprising the carbon material for a polymer electrolyte fuel cell catalyst support according to any one of claims 1 to 3.

5. A fuel cell comprising the catalyst layer for a polymer electrolyte fuel cell according to claim 4.

6. 6. The fuel cell in accordance with claim 5, wherein the catalyst layer for a polymer electrolyte fuel cell is a catalyst layer on a cathode side.

Citation Information

Patent Citations

  • Worm-hole-like mesoporous carbon carrier-loaded PtRu catalyst

    CN107565141A

  • Porous carbon material and method of producing the same

    JP2015164889A

  • Porous carbon, and production method thereof

    JP2019119632A

  • Carbon material for polymer electrolyte fuel cell catalyst carrier, catalyst layer for polymer electrolyte fuel cell and polymer electrolyte fuel cell

    JP2020042927A

  • Carbon material for use as catalyst carrier

    WO2014129597A1